2001
DOI: 10.1152/jn.2001.86.5.2571
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Pyramidal Cell Activity Encodes Conditioned Stimulus Predictive Value During Classical Conditioning in Alert Cats

Abstract: We have recorded the firing activities of hippocampal pyramidal cells throughout the classical conditioning of eyelid responses in alert cats. Pyramidal cells (n = 220) were identified by their antidromic activation from the ipsilateral fornix and according to their spike properties. Upper eyelid movements were recorded with the search coil in a magnetic field technique. Latencies and firing profiles of recorded pyramidal cells following the paired presentation of conditioned (CS) and unconditioned (US) stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 49 publications
10
50
0
Order By: Relevance
“…According to the present results, the maximum instantaneous frequency reached by type A (Gruart et al, 2000) interpositus neurons increased during the successive conditioning sessions, reaching mean amplitude values of Ϸ150 spikes/s during the first (C01) conditioning session and up to Ϸ320 spikes/s during the 10th (C10) session. The slope of this increase (0.14 spikes/s per trial) is similar to values reported for orbicularis oculi motoneurons (Trigo et al, 1999), interpositus neurons (Gruart et al, 2000), and hippocampal CA3 and CA1 pyramidal neurons (Mú nera et al, 2001) during associative learning using both delay and trace conditioning procedures in alert behaving cats. This important finding reinforces the hypothesis that associative learning using classical conditioning procedures evokes a functional state in many different neuronal centers, characterized by a common increase in firing rate, and not necessarily related with the specific function fulfilled by each neural site (Delgado-García and Gruart, 2002).…”
Section: The Posterior Interpositus Nucleus As An Enhancer Of Acquiresupporting
confidence: 83%
“…According to the present results, the maximum instantaneous frequency reached by type A (Gruart et al, 2000) interpositus neurons increased during the successive conditioning sessions, reaching mean amplitude values of Ϸ150 spikes/s during the first (C01) conditioning session and up to Ϸ320 spikes/s during the 10th (C10) session. The slope of this increase (0.14 spikes/s per trial) is similar to values reported for orbicularis oculi motoneurons (Trigo et al, 1999), interpositus neurons (Gruart et al, 2000), and hippocampal CA3 and CA1 pyramidal neurons (Mú nera et al, 2001) during associative learning using both delay and trace conditioning procedures in alert behaving cats. This important finding reinforces the hypothesis that associative learning using classical conditioning procedures evokes a functional state in many different neuronal centers, characterized by a common increase in firing rate, and not necessarily related with the specific function fulfilled by each neural site (Delgado-García and Gruart, 2002).…”
Section: The Posterior Interpositus Nucleus As An Enhancer Of Acquiresupporting
confidence: 83%
“…However, Delgado-Garcia and colleagues have reported that CA1 pyramidal cells in a group of cats that underwent trace eyeblink conditioning with a 520-ms CS-US interval (20-ms CS followed by a 500-ms trace period prior to US delivery) showed increases to CS and US onset from the beginning of CS-US presentations. Similar increases in pyramidal cell activity to CS and US onset were evident in a 500-ms delay procedure (Munera, Gruart, Munoz, Fernandez-Mas, & Delgado-Garcia, 2001), suggesting that the hippocampus may not differentiate between delay and trace conditioning at the level of single-unit activity. The amount of pyramidal cell activation to CS onset was reported to increase as delay or trace conditioning progressed.…”
Section: Introductionmentioning
confidence: 91%
“…In the only published study to match CS-US intervals and record from CA1 pyramidal cells during delay and trace eyeblink conditioning, CA1 pyramidal cell activation developed primarily to CS and US onset during both delay and trace eyeblink conditioning in the cat, and increased in magnitude to CS onset as conditioning progressed. However, an unusually short CS (20-ms) was used during trace conditioning and animals were given extensive (240 trials) CS preexposure (Munera et al, 2001), so the generality of these results for typical delay and trace conditioning remained in question. For example, CS preexposure attenuates CR-related hippocampal CA1 activation during subsequent conditioning (Katz, Rogers, & Steinmetz, 2002).…”
Section: The Involvement Of the Hippocampal Ca1 Field In Trace Conditmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, human imaging studies implicate the hippocampus and its surrounding input and output structures in the discrimination of contextual cues as well as the processing of aversive conditioned stimuli (Buchel et al, 1999;Bar and Aminoff, 2003). Finally, electrophysiological recordings in behaving animals show that the frequency of CA1 pyramidal neuron firing encodes information about the strength of conditioning to aversive stimuli (Munera et al, 2001), suggesting that cognitive circuits in the brain play a critical role in associative processing of aversive stimuli. Defects in hippocampal function at the cellular level have been documented in 5-HT1AR KO mice, including decreased paired pulse inhibition and increased basal excitability and dendritic arborization (R Hen and J Monckton, personal communication) in CA1 pyramidal neurons.…”
Section: Role Of the Hippocampus In The 5-ht1ar Ko Anxiety Phenotypementioning
confidence: 99%